The role of human papillomavirus in advanced laryngeal squamous cell carcinoma - Fauziah Fardizza; Bambang Hermani; Susyana Tamin (Oto Rhino Laryngologica Indonesiana, 2016)
Background: Many studies had been conducted regarding the association of human papillomavirus (HPV) with laryngeal cancer. HPV was assumed to be one of the etiology of squamous cell carcinoma (SCC) besides smoking and alcohol consumption. Neck lymph node metastasis which is found in advanced laryngeal cancer could decrease the 5-year survival rate up to 50%. Purpose: This study aimed to investigate the role of HPV infections in the oncogenesis of the advanced laryngeal SCC and to evaluate the role of HPV in neck metastasis. Methods: Cross-sectional, double blind study with planned data collection. Data were taken from Formalin Fixed Paraffin Embedded (FFPE) of laryngeal cancer specimen after laryngectomy. Samples were analyzed by nested Polymerase Chain Reaction (PCR) and continuous flow-through hybridization for genotyping. Expression of Epidermal Growth Factor Receptor (EGFR), and Vascular Endothelial Growth Factor (VEGF) as metastasis biomarker were evaluated by immunohistochemistry. Results: Overall HPV proportion in laryngeal cancer was 28.7%. A total of 9% laryngeal cancer patients were infected with high risk HPV type and HPV 16 was found in 5 out of 7 samples. Mantel-Haenszel multivariate analysis found that HPV infection did not play a role in neck metastasis even though there were positive evidences of metastasis biomarker. On the contrary, in the absent of HPV, high expression metastasis biomarkers increased the risk of neck nodes metastasis: in EGFR 3.38 and VEGF 5.14 fold. Conclusion: HPV was found to be an oncogenic factor of laryngeal SCC, and HPV 16 was the most frequently observed type of HPV. HPV had protective function towards lymph node metastasis.Keywords: Human papillomavirus, advanced laryngeal squamous cell carcinoma, expression of epidermal growth factor receptor, vascular endothelial growth factor, formalin fixed paraffin embeddedABSTRAK Latar belakang: Berbagai penelitian telah dilakukan untuk melihat hubungan antara Human papillomavirus (HPV) dengan karsinoma sel skuamosa (KSS) laring. HPV dianggap sebagai etiologinya, selain dari merokok dan konsumsi alkohol. Metastasis kelenjar getah bening (KGB) leher merupakan salah satu faktor yang menurunkan angka kesintasan lima tahun sebanyak 50% dan sering kali terjadi pada KSS laring yang telah lanjut. Tujuan: Penelitian ini ingin mengetahui peran HPV sebagai faktor onkogenesis dan faktor risiko kejadian metastasis KGB leher pada KSS laring lanjut. Metode: Cross-sectional, double blind study dengan pengumpulan data sekunder dari rekam medis. Data diambil dari parafin blok pasien KSS laring yang telah dilaringektomi. Semua data dianalisis dengan nested Polymerase Chain Reaction (PCR), dilanjutkan dengan flow-through hybridization untuk identifikasi tipe virus HPV. Dilakukan juga pemeriksaan imunohistokimia terhadap biomarka penanda metastasis yaitu Expression of Epidermal Growth Factor Receptor (EGFR), dan Vascular Endothelial Growth Factor (VEGF). Hasil: Secara keseluruhan didapatkan proporsi HPV pada KSS laring sebanyak 28,7%. Terdapat infeksi HPV tipe risiko tinggi pada 9% KSS laring, dan HPV 16 ditemukan pada 5 dari 7 sampel. Analisis multivariat Mantel-Haenszel mendapatkan infeksi HPV tidak berperan terhadap kejadian metastasis leher, meskipun didapati adanya biomarka penanda metastasis yang tinggi. Sebaliknya, pada ketiadaan infeksi HPV, adanya ekspresi biomarka metastasis yang tinggi meningkatkan risiko terjadinya metatasis KGB lokoregional pada EGFR 3,38 kali dan VEGF 5,14 kali. Kesimpulan: HPV dianggap sebagai faktor onkogenik KSS Laring, dan HPV 16 merupakan tipe yang paling sering ditemukan. HPV mempunyai fungsi protektif terhadap kejadian metastasis KGB lokoregional.Kata kunci: Human papillomavirus, advanced laryngeal squamous cell carcinoma, expression of epidermal growth factor receptor, vascular endothelial growth factor, formalin fixed paraffin embedded